Metodologías activas y su influencia en el aprendizaje virtual de los estudiantes de la Unidad Educativa 6 de Octubre, Ventanas-Los Ríos - Peña Vasquez, Hugo Adrian (2022)
In the document, an investigation is carried out on Active Methodologies and their influence on the virtual learning of the students of the Educational Unit "October 6", of the Ventanas canton, province of Los Ríos, Ecuador, which arises from the need to improve the learning of the students of First of Baccalaureate motivating the learning through the integration of tics resources in the development of the teaching methodologies. The research is carried out following a systematic structure where data was obtained from those involved, which were then contrasted with theoretical supports and finally the approach of an alternative solution. It is identified in the study that teachers use active methodologies, but there are certain drawbacks when including different ICT resources. The types of research applied are descriptive, bibliographic and field, the data collection instruments were based on a survey applied to the students of the first year of high school where clear and precise results were obtained; that led to the deduction of including tics in the application of these methodologies, for this, some digital platforms of easy access and management that efficiently contribute to student learning are included in the document.